Summer Phytoplankton Blooms Induced by Upwelling in the Western South China Sea - Chen, Ying; Shi, Haiyi; Zhao, Hui (Frontiers in Marine Science, 2021)
During summer, phytoplankton blooms occur frequently off the southeast Vietnam coast in the western South China Sea. Using multi-source remote sensing data, including sea surface temperature, sea surface wind, aerosol optical thickness, sea level anomalies and chlorophyll-a data from 1998 to 2020 as well as in situ observations analyzed data, we report the patterns of spatial variation of summer phytoplankton blooms in this region. Partial correlation and multiple stepwise linear regression analyses reveal Ekman transport and Ekman pumping velocity exert a greater impact on the summer phytoplankton blooms than other environmental factors, suggesting that the phytoplankton blooms in the region may be mainly triggered by enhanced nutrients by wind-induced upwelling and vertical mixing. Aerosol optical thickness only weakly correlates with Chl-a concentration in the region, probably these prominent abundant nutrients in the region come from upwelling and convective-overturn. A northeastward jet causes the distribution of high Chl-a in the western South China Sea to be plume-shaped. A new finding in our study is that the northward current in this area may cause the northward deviation of phytoplankton blooms from areas of upwelling.